Comparative evaluation of PCR amplification of RLEP, 16S rRNA, rpoT and Sod A gene targets for detection of M. leprae DNA from clinical and environmental samples. Issue 1 (March 2015) - Turankar, Ravindra P.; Pandey, Shradha; Lavania, Mallika; Singh, Itu; Nigam, Astha; Darlong, Joydeepa; Darlong, Fam; Sengupta, Utpal
Abstract Purpose PCR assay is a highly sensitive, specific and reliable diagnostic tool for the identification of pathogens in many infectious diseases. Genome sequencing Mycobacteriumleprae revealed several gene targets that could be used for the detection of DNA from clinical and environmental samples. The PCR sensitivity of particular gene targets for specific clinical and environmental isolates has not yet been established. The present study was conducted to compare the sensitivity of RLEP, rpoT, Sod A and 16S rRNA gene targets in the detection of M. leprae in slit skin smear (SSS), blood, soil samples of leprosy patients and their surroundings. Method Leprosy patients were classified into Paucibacillary (PB) and Multibacillary (MB) types. Ziehl–Neelsen (ZN) staining method for all the SSS samples and Bacteriological Index (BI) was calculated for all patients. Standard laboratory protocol was used for DNA extraction from SSS, blood and soil samples. PCR technique was performed for the detection of M. leprae DNA from all the above-mentioned samples. Results RLEP gene target was able to detect the presence of M. leprae in 83% of SSS, 100% of blood samples and in 36% of soil samples and was noted to be the best out of all other gene targets (rpoT, Sod A and 16S rRNA). It was noted that the RLEP gene target was able to detect the highest number (53%) of BI-negative leprosy patients amongst all the gene targets used in this study. Conclusion Amongst all the gene targets used in this study, PCR positivity using RLEP gene target was the highest in all the clinical and environmental samples. Further, the RLEP gene target was able to detect 53% of blood samples as positive in BI-negative leprosy cases indicating its future standardization and use for diagnostic purposes.